The Effect Of Occupational Safety And Health And Organizational Commitment On Soldier Performance By Using The Approach Partial Least Square – Sem Analysis - Purnamasari, Ari Tri; Paramarta, Vip; Kosasih, Kosasih; Wirawan, Chevie; M.A, Etty Sofia (Universitas Pahlawan Tuanku Tambusai, 2024)
The background of this research is that the performance of Paspampres soldiers has yet to be discovered, and the factors that affect the performance of Paspampres soldiers still need to be discovered. Basedoon the background,,thissstudy attempts to examine the impacttof Occupational Safety and Health and OrganizationallCulture partially and directly on Soldier Performance and indirect influence through the intervening variable of Organizational Commitment. A descriptive verificative explanatory design wasuused in this research. In theqquantitative phase, The instrument offresearch wasuused to perform a survey on 144 Soldier which was then descriptively examine. . The data analysis technique uses SEM-PLS to test the outer model, inner model, and hypothesis test. The result show that the Paspampres Soldier Organization's Commitment and OccupationallSafety anddHealth have a positive and significant relationship..Occupational Safety and Health also positively and significantly affects Paspampres Soldiers' Performance, while Organizational Commitment has no significant affect and has a negative impact on Paspampres Soldiers' Performance. Moreover, Occupational Safety and Health and OrganizationalcCommitment both positivelyyand significantly affect Paspampres Soldiers' Performance at the same time. Research uses organizational commitment as a variable on soldier performance and does not have a significant effect in this research. Several previous research have examined the effect of organizational commitment variables onpperformance, showing significant differences in the research results that support the theory and suggest for more research.